MORFO-CLINICAL GROUND OF RHYNOPLASTIC BY ARTERIOVASAL SHREDS FROM LOBAL SKIN - Ol'khovskiy, V.O.; Ruzin, G.P. (World of Medicine and Biology, 2010)
Rinoplastic by a arteriovasal shred from the lobal skin with including of superficial temporal, supratrochlear and supraoptical arteries, the method of which is presented authors, allows one-time to remove difficult defects of a nose. Thus by shreds with axial circulation of blood it is succeeded to form carried even in case that for a patient the terms of microvasculation are sharply broken. The functional and cosmetic result of these operations is satisfactory.